2014
DOI: 10.1016/j.ijid.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of innate immunity in the pathogenesis of otitis media

Abstract: Summary Otitis media (OM) is a public health problem in both developed and developing countries. It is the leading cause of hearing loss and represents a significant healthcare burden. In some cases, acute OM progresses to chronic suppurative OM (CSOM), characterized by effusion and discharge, despite antimicrobial therapy. The emergence of antibiotic resistance and potential ototoxicity of antibiotics has created an urgent need to design non-conventional therapeutic strategies against OM based on modern insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 135 publications
(125 reference statements)
1
37
0
Order By: Relevance
“…Upregulation of these innate mechanisms is crucial for the rapid resolution of OM 81 . However, these cytokines and antimicrobial proteins can also have a pathophysiological role 80,82 that is characterized by persistent inflammation of the middle ear, as observed in CSOM 83 . The predominant bacterial pathogens for CSOM -Pseudomonas aeruginosa and Staphylococcus aureus 83,84 -form biofilms with other otopathogens and elicit an increased innate inflammatory responses, which might contribute to the chronicity of OM and progression to CSOM despite appropriate intervention 84 .…”
Section: Middle Ear Effusion (Mee) 178mentioning
confidence: 99%
“…Upregulation of these innate mechanisms is crucial for the rapid resolution of OM 81 . However, these cytokines and antimicrobial proteins can also have a pathophysiological role 80,82 that is characterized by persistent inflammation of the middle ear, as observed in CSOM 83 . The predominant bacterial pathogens for CSOM -Pseudomonas aeruginosa and Staphylococcus aureus 83,84 -form biofilms with other otopathogens and elicit an increased innate inflammatory responses, which might contribute to the chronicity of OM and progression to CSOM despite appropriate intervention 84 .…”
Section: Middle Ear Effusion (Mee) 178mentioning
confidence: 99%
“…However, the dysfunction of immune system can result in a higher susceptibility and vulnerability to bacterial infections, which stand out as the most common cause of diseases [2]. In recent decades, evidences suggested that the modulation of innate immunity has a significant impact on the host's ability to respond to a diverse array of pathogens [3][4][5][6]. Up to date, several types of immunomodulators have been developed, including mammalian proteins and chemical synthetic drugs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Complement components C3 and C4 increased in OM patient's blood because of the important role of these complement components in the inflammatory process during infections, these results are also documented by [21] they fully described complement role in the middle ear infections and they attributed that increase to the increase of the complement and inflammatory mediators production during inflammation of middle ear after activation of phagocytic cells. The authors [7,22] stated that many complement proteins and Cytokines levels usually rise during inflammatory diseases as a part of innate immunity and as a start of specific Humoral response and that is supporting to the findings of our study.…”
Section: Discussionmentioning
confidence: 63%